Clinical characteristics and prognosis of anti-γ-aminobutyric acid-B receptor encephalitis: A single-center, longitudinal study in China - Feng, Xuedan; Zhang, Yujing; Gao, Yu; Zhang, Jing; Yu, Shasha; Lv, Jing; Zu, Yu; Wang, Lin; Wang, Xiangbo (Frontiers in Neurology, 2022)
Objective：Anti-γ-aminobutyric acid-B receptor (GABABR) encephalitis is a rare type of autoimmune encephalitis. There are only a few, small, published studies regarding prognosis, so prediction of prognosis is of limited accuracy. We identified 36 cases of GABABR encephalitis in China. Here, we present these patients’ clinical characteristics and long-term outcomes. Methods： We collected and retrospectively analyzed the clinical data of 36 patients with anti-GABABR encephalitis from Beijing Fengtai Youanmen Hospital. Results： The study cohort comprised 36 patients of anti-GABABR encephalitis of median age 61 years (range: 11–77), 27 of whom were male. The main clinical manifestations were epilepsy (88.9%, 33/36), psychiatric disorders (94.4%, 31/36) and cognitive impairment (91.7%, 32/36). Tumors were identified in 17 (47.2%) patients. First-line immunotherapy was administered to 32 patients, 29 of whom (90.6%) responded favorably. During a median follow-up of 17 months (range:1–66 months), 19 patients had good outcomes (Modified Ranking Scale [mRS≤2]), 2 had moderate to severe neurological dysfunction (mRS score 3 or 4), 15 (41.7%) died (mRS 6), and 7 (19.4%) relapsed. Age (P=0.040), disturbance of consciousness (P=0.008), admission to the Neurology Intensive Care Unit (P=0.007), mechanical ventilation (P=0.017), more numerous clinical manifestations (P=0.001), comorbid malignancy (P=0.018), multiple anti-neuronal antibodies (P=0.037), and hyponatremia (P=0.039) differed significantly between patients with good outcomes (mRS 0–2) and those with poor outcomes (mRS 3–6). Conclusion: Men aged 50–70 years accounted for most of the patients with anti-GABABR encephalitis in our case series. The main clinical manifestations were epilepsy and neuropsychiatric dysfunction. The participants often had concomitant lung cancer, particularly small-cell lung cancer. Patients with lung tumors and/or serious manifestations usually had a poor prognosis with high mortality. Early identification and treatment of tumors improved the por prognosis to some extent.